A lost track in ICHD 3 beta: A comprehensive review on osmophobia. (February 2018) - Zanchin, Giorgio; Fuccaro, Matteo; Battistella, Pierantonio; Ermani, Mario; Mainardi, Federico; Maggioni, Ferdinando
Background: Osmophobia (Os) has been reported to be much more prevalent in migraine (M) than in other primary headaches, and its high specificity in the differential diagnosis between M and tension-type headache (TTH) has been reported. Os was included in the ICHD II Appendix as a diagnostic criterion of M. It disappeared in ICHD-3 beta. To understand this choice, we reviewed the literature after 2004. Methods: This was a systematic review. We searched in PubMed, MEDLINE and Cochrane library for "osmophobia", "odour/odorphobia AND headache", "odour/odor hypersensitivity AND headache" and "olfactory hypersensitivity AND headache". Results: 112 papers cited Os as an accompanying symptom of headache; 16 focused on Os in M diagnosis. With the data from 40 articles, we calculated the pooled prevalence of Os in 14, 360 patients (2281 pediatric) affected by M (n = 12, 496) and TTH (n = 1864). In M, the prevalence was 48.5% (CI 95% 41.4 to 55.8%) in adults and 23.4% (CI 95% 15.7 to 33.4%) in pediatric patients; in TTH, the prevalence was 8.9% (CI 95% 4.6 to 13.5%) in adults and 7.9% (CI 95% 3.3 to 18.1%) in pediatric patients. Ten of these papers allowed us to calculate the sensibility and specificity of Os in differential diagnosis between M and TTH. In adults, the value of specificity was 94.1% (CI 95% 88.9 to 96.9%), and sensitivity was 51.4% (CI 95% 38.4 to 64.2%). In pediatric patients, specificity was 92.0% (CI 95% 81.9 to 96.7%), and sensitivity was 22.1% (CI 95% 10.1 to 41.8%). Conclusion: The literature endorses the inclusion of Os among M diagnostic criteria. On this ground, the decision to remove Os from ICHD 3 beta appears unjustified and a revision of this choice is recommended.